Pengaruh Likuiditas dan Solvabilitas Terhadap Rentabilitas Modal Sendiri pada PKPRI di Kabupaten Simalungun - Ady Inrawan; Jubi Jubi; Hery Pandapotan Silitonga; Acai Sudirman (Accounthink : Journal of Accounting and Finance, 2022)
Creating a just and prosperous society is one of the ideals or goals of Indonesia's national development. Various types of businesses are carried out to obtain venture capital in conducting economic activities, the existence of financial institutions, especially cooperatives, is participating in supporting business capital. This study aims to (1) test and analyze the effect of liquidity on the profitability of their own capital, (2) test and analyze the effect of solvency on the profitability of their own capital, (3) test and analyze the effect of liquidity and solvency together on the profitability of their own capital. The data used is quantitative data sourced from secondary data. The analytical method used is multiple linear regression analysis. The results of this study indicate that (1) liquidity does not affect the profitability of equity capital, (2) solvency affects the profitability of equity capital, (3) liquidity and solvency together influence the profitability of equity capital.